2018
DOI: 10.5152/turkjsurg.2018.3952
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of St. John’s wort in the hepatic ischemia/reperfusion injury in rats

Abstract: The obtained results indicate protective effects of St. John's wort on the ischemia/reperfusion injury through various mechanisms, and we are able to suggest that St. John's wort can clinically create a new therapeutic principle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
2
8
0
Order By: Relevance
“…Studies have shown a reduction in Na + -K + -ATPase level after hepatic ischemia reperfusion (32,33). Our study revealed that Na + -K + -ATPase activity in the liver tissue was lower in the IR group when compared to the control group.…”
Section: A B C Dsupporting
confidence: 41%
See 1 more Smart Citation
“…Studies have shown a reduction in Na + -K + -ATPase level after hepatic ischemia reperfusion (32,33). Our study revealed that Na + -K + -ATPase activity in the liver tissue was lower in the IR group when compared to the control group.…”
Section: A B C Dsupporting
confidence: 41%
“…Luminol hydroxyl radical is an indicator of the formation of reactive oxygen metabolites such as hydrogen peroxide and hypochloric acid. Lusigenin marks the formation of superoxide anion radical (33). They indirectly indicate the level of ROM-mediated tissue injury.…”
Section: A B C Dmentioning
confidence: 99%
“…In the present study hepatic IRI resulted in a significant elevation in MPO content. These results go in harmony with many of previous studies either directly (46) or remotely (47) which could be attributed to the induced expression of NF-κB and/or IL-1β that accomplished in the present work. The pretreatment with CEL could provide a significant cut down in the renal MPO content.…”
Section: Beta-actin Hsf-1 B Hsf-1 Hsp90 a Hsp90supporting
confidence: 93%
“…Sodium/potassium adenosine triphosphatase enzyme takes part in the structure and physiology of liver cells by providing sodium and potassium balance in all cell membranes (45). According to studies, it has been observed that BDL reduces the levels of Na + /K + -ATPase in liver tissue (46,47).…”
Section: Discussionmentioning
confidence: 99%